Kajian Kondisi Perikanan Di Danau Laut Tawar Aceh Tengah - Indra Indra (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. Besides as a tourism area, Laut Tawar Lake also as a place to earn a living for fishermen around it. The aims of the study was to provide an overview of the condition of fisheries in Laut Tawar Lake. The method used was a survey method. The population were fishermen that consist of capture fishery dan culture fishery. The sampling technique used was sratified random sampling. The number of samples was 30 people that consist of 15 fishermen as cupture fishery dan 15 fishermen as culture fishery. Data was analyzed by descriptive quantitative. The results showed that the number of catches have declined in recent years. These shows that there has been a degradation of fish resources (stock) in the Laut Tawar Lake, as a result of overexploitation or overfishing. There has been a development of aquaculture significantly in recent years, this was due to meet the public demand for fish by increasing along with population growth, knowledge about nutrition and income of society. Looking ahead, it is necessary for the optimal management of managing the resource due to its sustainability, such as through effort rationalization, setting the open and close, and the Marine Protected Area.